Tactile material for the prevention of blood hypertension in blind people - Lorita Marlena Freitag Pagliuca; Kátia Nêyla de Freitas Macêdo; Grazielle Roberta Freitas da Silva (Rev Rene)
Blood hypertension affects many people and can be controlled through health education. Blind people find it difficult to have access to educative material, for they usually are written. This study aimed at elaborating educative material and method about blood hypertension prevention and control for those patients. This study was held in an association of blind people, in Fortaleza city (Ceará), from December 2002 to February 2003. One created an artificial longitudinally cut heart, with atriums and ventricles, the main veins and arteries. These structures were built in materials of different textures. The blind, during nursing appointments, seemed to be satisfied with the technology and suggested changes. One concluded that the creation of new Nursing technology used for education and health with blind people is easily obtained and handled.